Protection of Temporary Workers in 2008/104 EC Directive on Temporary Agency Work - Flexibility or Security? - Койчева, Райна (Научни трудове, 2018)
This report is an attempt to critically analyze the provisions of Directive 2008/104 EC on temporary agency work aimed at guaranteeing the rights of temporary workers.The report aims to clarify how the Directive managed to find a reasonable compromise between more flexibility in regulating labor relations and the providing of adequate level of protection for temporary workers.The conclusion of the author is that Directive 2008/104 EC does not sufficiently protect temporary workers. It gives priority to flexibility to the detriment of security.